A Novel SNP-STR System Based on a Capillary Electrophoresis Platform - Jian, Hui; Wang, Li; Lv, Meili; Tan, Yu; Zhang, Ranran; Qu, Shengqiu; Wang, Jijun; Zha, Lagabaiyila; Zhang, Lin; Liang, Weibo (Frontiers in Genetics, 2021)
Various compound markers encompassing two or more variants within a small region can be regarded as generalized microhaplotypes. Lots of this kind of markers have been investigated for various forensic purposes, such as individual identification, deconvolution of DNA mixtures, or forensic ancestry inference. SNP-STR is a compound biomarker composed of a single nucleotide polymorphism (SNP) and a closely linked short tandem repeat polymorphism (STR), possessing advantages of both SNPs and STRs. In addition, in conjunction with a PCR technique based on amplification refractory mutation system (ARMS), SNP-STRs can be used to forensic unbalanced DNA mixtures analysis based on capillary electrophoresis (CE), which is the most commonly used platform in worldwide forensic laboratories. Our previous research has reported 11 SNP-STRs, but few of them are derived from the commonly used STR loci, for which existing STR databases can be used as a reference. For maximum compatibility with existing DNA databases, in this study, we screened 18 SNP-STR loci, of which 14 are derived from the expanded CODIS core loci set. Stable and sensitive SNP-STR multiplex PCR panels based on CE platform were established. Assays on simulated two-person DNA mixtures showed that all the allele-specific primers could detect minor DNA components in 1:500 mixtures. Population data based on 113 unrelated Chengdu Han individuals was investigated. A Bayesian framework was developed for the likelihood ratio (LR) evaluation of SNP–STR profiling results obtained from two-person mixtures. Furthermore, we report on the first use of SNP-STRs in casework to show advantages and limitations in practice. Comparing to 2.86×10^3 for autosomal STR kits, the combined LR reached 7.14×10^7 by using SNP-STR method in this casework example.